2005
DOI: 10.3171/spi.2005.3.5.0379
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical data on the craniocervical junction and their correlation with degenerative changes in 30 cadaveric specimens

Abstract: >Object. The goal of this project was to measure vertebral dimensions at the craniocervical junction and to investigate degenerative changes in this region and their correlations with the anatomical data. These studies will assist in an understanding of biomechanical conditions in this region, which are clinically relevant in cases of cervicogenic headaches and vertigo. Methods. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
3
19
0
Order By: Relevance
“…Because of the advanced ages of the subjects, an analysis of the amount of degenerative joint disease present was completed. Severe degeneration of the A/O joints was rare, which is in agreement with the findings of Konig et al 11 Grade 0 (no sign of degeneration) and grade I (superficial degeneration) were observed in all 12 A/O joint surfaces. No grade II (cartilaginous disintegration) or grade III degeneration (appearance of subchondral bone in 50% of the articular surface) was observed using the Petersson classification.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…Because of the advanced ages of the subjects, an analysis of the amount of degenerative joint disease present was completed. Severe degeneration of the A/O joints was rare, which is in agreement with the findings of Konig et al 11 Grade 0 (no sign of degeneration) and grade I (superficial degeneration) were observed in all 12 A/O joint surfaces. No grade II (cartilaginous disintegration) or grade III degeneration (appearance of subchondral bone in 50% of the articular surface) was observed using the Petersson classification.…”
Section: Methodssupporting
confidence: 92%
“…No grade II (cartilaginous disintegration) or grade III degeneration (appearance of subchondral bone in 50% of the articular surface) was observed using the Petersson classification. 11,12 This study was reviewed by the Sherman College institutional review board and was found to be exempt from regulations mandated by US Federal guidelines relative to the use of live human subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Table 2 reveals that there is similarity between the values of the present study and most of the previous studies. Konig et al [17] has used a grid system to measure the dimensions which might have lead to higher values. Cattrysse et al [18] evaluated pairs of atlas and axis vertebrae from same spine and found that the C1 IAF has lower APD than the SAF of C2.…”
Section: Methodsmentioning
confidence: 99%
“…These true synovial joints allow articulation with the occipital condyles and the axis respectively. The atlantooccipital joints orientation at caudal angles of 129 degrees from lateral to medial limits the rotation possible, compared with the atlantoaxial joint with a cranially biased angulation of between 130-135 degrees, where much greater rotation is possible (Konig et al 2005). A posterior tubercle is found in the midline posteriorly providing attachment for the rectus capitis and the ligamentum nuchae.…”
Section: Atlasmentioning
confidence: 92%
“…The greater occipital nerve of Arnold is found 15mm off the midline, the importance of preservation through a strict subperiosteal surgical approach lying in posterior scalp numbness or neuralgia should the nerve be damaged (Vital et al 1989). The occipital condyles, which function as skull-base weight-bearing facets, angle medially and inferiorly at average angles of 55 and 117.5 degrees when viewed from behind (Konig et al 2005). These shape of these condyles positioned on either side of the foramen magnum allow the skull articulate with the cervical spine, whilst the angles prevent excessive axial rotation at the craniocervical junction (Noble & Smoker 1996).…”
Section: Occipital Bonementioning
confidence: 99%